DEVELOPMENT AND CHARACTERIZATION OF DORZOLAMIDE LOADED NOVASOMES FOR THE MANAGEMENT OF GLAUCOMA - Yogyata S Pathare; Manoj S Tare; Sandeep S Pathare; Kazi Mohamad Shayan (The Bioscan, 2025)
A chronic eye condition called glaucoma is characterized by damage to the retinal nerve and progressive vision loss, primarily brought on by high intraocular pressure (IOP). It is one of the main causes of permanent blindness in the world. Currently, the first line of treatment for glaucoma involves pharmacological reduction of IOP through topical administration of drugs. However, because of the anatomical and physiological barriers in the eye, less than 5% of the injected dose usually reaches intraocular tissues. The goal of the research was to develop novasomes to create an efficient medication delivery system for ocular targeting. The solvent evaporation approach was used to develop dorzolamide novasomes utilizing different ratios of cholesterol and free fatty acids (linoleic acid). It was optimized by 32 factorial design. Free fatty acid and cholesterol concentrations were the factors under investigation, along with their effects on particle size, polydispersity index, zeta potential, entrapment efficiency, and in vitro drug release. Particle size of all factorial batches was found between 54.1 nm to 434 nm. Batch F6 containing cholesterol and linoleic acid 1:2 proportion showed highest entrapment (98%). The amount of dorzolamide released in vitro from the prepared novasomal dispersions loaded with dorzolamide ranged from 62.76 to 99.76 % and release profile of novasomal batches comparing to eye suspension were better . Ex vivo chicken eye irritation study was performed to check irritation potential of dorzolamide loaded novasomes. In summary, dorzolamide novasomes is an efficient and versatile drug delivery approach which demonstrates significant potential in controlling glaucoma.